2014
DOI: 10.1093/cid/ciu918
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Persistence of Zoster Vaccine Efficacy

Abstract: Estimates of vaccine efficacy decreased over time in the LTPS population compared with modeled control estimates. Statistically significant vaccine efficacy for HZ BOI persisted into year 10 postvaccination, whereas statistically significant vaccine efficacy for incidence of HZ persisted only through year 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(177 citation statements)
references
References 21 publications
7
163
0
7
Order By: Relevance
“…Thus, the FDA has approved its administration in healthy adults ≥ 50 years of age, with contraindications including anaphylaxis to gelatin or neomycin, immunosuppression, immunodeficiency and pregnancy. The SPS demonstrated efficacy for 4 years after vaccination, while subsequent studies (52,53) indicated efficacy for 8 years (54). Currently, CDC does not recommend booster doses of zoster vaccine, but may in the future.…”
Section: Zostavaxmentioning
confidence: 98%
“…Thus, the FDA has approved its administration in healthy adults ≥ 50 years of age, with contraindications including anaphylaxis to gelatin or neomycin, immunosuppression, immunodeficiency and pregnancy. The SPS demonstrated efficacy for 4 years after vaccination, while subsequent studies (52,53) indicated efficacy for 8 years (54). Currently, CDC does not recommend booster doses of zoster vaccine, but may in the future.…”
Section: Zostavaxmentioning
confidence: 98%
“…In the LTPS study, parts of the cohort of the SPS and STPS studies were followed up for a period of up to 11 years after vaccination [39]. The study was conducted from March 2006 to December 2010.…”
Section: Long-term Persistence Substudy (Ltps)mentioning
confidence: 99%
“…In additional substudies 159,160 , efficacy for burden of disease persisted for 10 years after vaccination but efficacy for the incidence of zoster persisted only for 8 years 160 . The CDC currently does not recommend booster doses of the zoster vaccine, but it might do in the future.…”
Section: Preventionmentioning
confidence: 99%